Depressive Symptoms as a Predictor of Quality of Life in Cerebral Small Vessel Disease, Acting Independently of Disability; a Study in Both Sporadic Small Vessel Disease and Cadasil. Issue 7 (October 2013) - Brookes, Rebecca L.; Willis, Thomas A.; Patel, Bhavini; Morris, Robin G.; Markus, Hugh S.
Background: Cerebral small vessel disease causes lacunar stroke, and more recently has been implicated as a cause of depression. Factors causing reduced quality of life in small vessel disease, including the relative contributions of disability and depressive symptoms, remain uncertain. Methods: One hundred patients with small vessel disease and 55 controls completed the Stroke-Specific Quality of Life scale. The protocol was repeated in 40 patients with the young-onset genetic form of small vessel disease, cerebral autosomal dominant arteriopathy with sub-cortical infarcts and leukoencephalopathy, and 35 controls. Disability, activities of daily living, cognition and depression were measured. Results: Quality of life was significantly lower in small vessel disease versus controls: mean (standard deviation), 196·8 (35·2) vs. 226·8 (15·3), P < ·0001. Depressive symptoms were the major predictor of quality of life, explaining 52·9% of variance. The only other independent predictor was disability, explaining an additional 18·4%. A similar pattern was found in the young-onset genetic group, with reduced quality of life 202·0 (29·7) vs. controls 228·6 (13·1) P < ·0001, and depressive symptoms accounting for 42·2% of variance. Disability explained an additional 17·6%. Relationships between depression and quality of life, and disability and quality of life were independent of one another. Conclusions: Depressive symptoms, often unrecognized, are a major determinant of reduced quality of life in small vessel disease. They account for greater reduction than, and are independent of, disability. This relationship may reflect the proposed causal association between white matter disease and depression. Treatment of depressive symptoms might significantly improve quality of life in small vessel disease.